Thematic Study of Management Verses and Their Relevance to Islamic Education - Selvy Yuspitasari; Mudzakir Mudzakir (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Islamic education management requires not only administrative efficiency but also strong integration of Qur’anic values to achieve holistic educational goals. Specific Background: Although the Qur’an contains numerous verses that reflect managerial principles—such as planning, leadership, deliberation, supervision, and accountability—many Islamic educational institutions have not yet fully integrated these values into management practices. Knowledge Gap: Existing studies rarely provide a thematic and systematic analysis of Qur’anic verses on management and their direct relevance to contemporary Islamic education management. Aims: This study aims to conduct a thematic analysis of management-related verses in the Qur’an and examine their applicability to the management of Islamic educational institutions. Results: The findings reveal that Qur’anic values such as trustworthiness, justice, deliberation, honesty, and responsibility offer a strong managerial framework that aligns with modern management functions, including planning, organizing, controlling, and evaluating. Novelty: This study provides an integrated thematic interpretation that bridges classical Qur’anic principles and modern educational management theory. Implications: Applying Qur’anic managerial principles can strengthen institutional governance, enhance educational quality, and support the development of holistic, value-based Islamic education systems. Highlights: Qur’anic values provide a comprehensive foundation for modern educational management. Management in Islamic education must integrate ethical, spiritual, and administrative principles. Thematic analysis reveals strong alignment between Qur’anic principles and core management functions. Keywords: Qur’anic Management, Islamic Education, Thematic Interpretation, Spiritual Values, Educational Leadership